21st-Century Narratives of World History
XXXIII, 412 p. 2 illus.
Keywords: This book makes a unique and timely contribution to world/global historical studies and related fields. It places essential world historical frameworks by top scholars in the field today in clear, direct relation to and conversation with one other, offering them opportunity to enrich, elucidate and, at times, challenge one another. It thereby aims to: (1) offer world historians opportunity to critically reflect upon and refine their essential interpretational frameworks, (2) facilitate more effective and nuanced teaching and learning in and beyond the classroom, (3) provide accessible world historical contexts for specialized areas of historical as well as other fields of research in the humanities, social sciences and sciences, and (4) promote comparative historiographical critique which (a) helps identify continuing research questions for the field of world history in particular, as well as (b) further global peace and dialogue in relation to varying views of our ever-increasinglyinterconnected, interdependent, multicultural, and globalized world and its shared though diverse and sometimes contested history.